The effect of periodontal treatment on hemoglobin a1c levels of diabetic patients: a systematic review and meta-analysis. - Xingxing Wang; Xu Han; Xiaojing Guo; Xiaolong Luo; Dalin Wang (PLoS ONE)
Background There is growing evidence that periodontal treatment may affect glycemic control in diabetic patients. And several systematic reviews have been conducted to assess the effect of periodontal treatment on diabetes outcomes. Researches of this aspect are widely concerned, and several new controlled trials have been published. The aim of this study was to update the account for recent findings. Methods A literature search (until the end of January 2014) was carried out using various databases with language restriction to English. A randomized controlled trial (RCT) was selected if it investigated periodontal therapy for diabetic subjects compared with a control group received no periodontal treatment for at least 3 months of the follow-up period. The primary outcome was hemoglobin A1c (HbA1c), and secondary outcomes were periodontal parameters included probing pocket depth (PPD) and clinical attachment level (CAL). Results Ten trials of 1135 patients were included in the analysis. After the follow-up of 3 months, treatment substantially lowered HbA1c compared with no treatment after periodontal therapy (-0.36%, 95%CI, -0.52% to -0.19%, P<0.0001). Clinically substantial and statistically significant reduction of PPD and CAL were found between subjects with and without treatment after periodontal therapy (PPD -0.42 mm, 95%CI: -0.60 to -0.23, P<0.00001; CAL -0.34 mm, 95%CI: -0.52 to -0.16, P=0.0002). And there is no significant change of the level of HbA1c at the 6-month comparing with no treatment (-0.30%, 95%CI, -0.69% to 0.09%, P=0.13). Conclusions Periodontal treatment leads to the modest reduction in HbA1c along with the improvement of periodontal status in diabetic patients for 3 months, and this result is consistent with previous systematic reviews. And the effect of periodontal treatment on HbA1c cannot be observed at 6-month after treatment.